Identification of key molecular components of the resistance of cherry tomato against phytophthora infestans (2012)
Cherry tomato Solanum lycopersicum var cerasiforme cv Matt’s wild cherry is a very resistant cultivar to most Phytophthora infestans isolates. Two isolates were identified, US940480 and US970001 that cause an incompatible and a compatible interaction respectively. US970001 is one of the few isolates producing a compatible interaction with this cultivar. To identify genes with a differential gene expression between compatible and incompatible interactions, gene expression patterns were analyzed with tomato cDNA microarrays including 12,899 independent tomato cDNA clones at different time points after inoculation. A diverse set of statistical tools were used to identify key components of the plant response to the pathogen. Forty-three genes were up-regulated during the incompatible reaction at time point 36 hours, 15 globally at all time points and twelve were found both in globally and at 36 hours. Northern blots analysis was performed to confirm differential expression showed by microarray analysis and to study the differential expression of more PR genes between compatible and incompatible interactions for this interaction.